1996
DOI: 10.1017/bjn19960129
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation by human faecal bacteria of total and purified dietary fibres from brown seaweeds

Abstract: The in vitro degradation of dietary fibre from three brown seaweeds (Himanthalia elongata, Laminaria digitata and Undaria pinnatiJda) was studied, using human faecal flora. Two sets of fibre were tested:(1) total algal fibres extracted from the whole algae, mainly composed of alginates, and (2) purified fibres (sulphated fucans, Na-alginates and laminarans) representative of those contained in the whole brown algae. Mannuronate, one algal component, was also investigated. Substrate disappearance and shortchain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 36 publications
4
54
0
Order By: Relevance
“…However, in separate studies on algal oligosaccharides, alginate oligosaccharides were not found to alter the total aerobe/anaerobe balance in faecal inoculum (Michel et al, 1999). In other faecal inoculum studies, the fermentability of faecal alginate is suggested as being much lower than the values quoted by Michel et al, (1996), as only 50% of alginate had disappeared after 24 h (Bobin-Dubigeon et al, 1997). Alginates appear to have a slightly lower fermentability in vivo in rats, as 64% of alginate is recovered in faeces upon initial feeding with alginate.…”
Section: Alteration Of Colonic Microfloramentioning
confidence: 81%
See 4 more Smart Citations
“…However, in separate studies on algal oligosaccharides, alginate oligosaccharides were not found to alter the total aerobe/anaerobe balance in faecal inoculum (Michel et al, 1999). In other faecal inoculum studies, the fermentability of faecal alginate is suggested as being much lower than the values quoted by Michel et al, (1996), as only 50% of alginate had disappeared after 24 h (Bobin-Dubigeon et al, 1997). Alginates appear to have a slightly lower fermentability in vivo in rats, as 64% of alginate is recovered in faeces upon initial feeding with alginate.…”
Section: Alteration Of Colonic Microfloramentioning
confidence: 81%
“…Although over 80% of alginate was degraded in 24 h incubation with faecal inoculum, levels of SCFA release were significantly lower than this (Michel et al, 1996). This could suggest that alginates are increasing the numbers of aerobes in the inoculum, therefore reducing the levels of measured SCFA released (due to the aerobic metabolism of alginate/SCFA), or that SCFA are not being produced as a byproduct of alginate metabolism.…”
Section: Alteration Of Colonic Microfloramentioning
confidence: 85%
See 3 more Smart Citations